Essential Oil Composition from The Flower, Leaf and Stem of Polygonum alpinum from Turkey - UCUNCU, OSMAN; YAYLI, NURAN; YASAR, AHMET; ALBAY, CANAN; YAYLI, NURETTIN; TERZIOGLU, SALIH (Asian Journal of Chemistry, 2010)
The volatile oil of Polygonum alpinum L. (Polygonaceae) was prepared by hydrodistillation of flower, leaf and stem and characterized by GC and GC-MS. A total of 44, 41 and 38 compounds were identified, constituting over 94.4, 96.3 and 97.2 % of oil composition of the flower, leaf and stem of P. alpinum, respectively. Esters were shown to be the main group of constituents (flower: 46.2 %, leaf: 59.1 %, stem: 82.5 %). The major components of the oils of P. alpinum were ethyl hexadecanoate (flower: 11.7 %, leaf: 15.0 %, stem: 21.1%), methyl linoleate (flower: 30.7 %, leaf: 11.7 %, stem: 36.7 %) and ethyl linoleate (leaf: 25.8 %, stem: 14.7 %). Terpenoids were the minor constituents in all parts (flower: 5.6 %, leaf: 11.0 %, stem: 6.4 %) of the P. alpinum.